Coordination of plant hydraulic and photosynthetic traits: confronting optimality theory with field measurements. Issue 3 (24th August 2021) - Xu, Huiying; Wang, Han; Prentice, I. Colin; Harrison, Sandy P.; Wright, Ian J.
Summary: Close coupling between water loss and carbon dioxide uptake requires coordination of plant hydraulics and photosynthesis. However, there is still limited information on the quantitative relationships between hydraulic and photosynthetic traits. We propose a basis for these relationships based on optimality theory, and test its predictions by analysis of measurements on 107 species from 11 sites, distributed along a nearly 3000‐m elevation gradient. Hydraulic and leaf economic traits were less plastic, and more closely associated with phylogeny, than photosynthetic traits. The two sets of traits were linked by the sapwood to leaf area ratio (Huber value, v H ). The observed coordination between v H and sapwood hydraulic conductivity ( K S ) and photosynthetic capacity ( V cmax ) conformed to the proposed quantitative theory. Substantial hydraulic diversity was related to the trade‐off between K S and v H . Leaf drought tolerance (inferred from turgor loss point, –Ψtlp ) increased with wood density, but the trade‐off between hydraulic efficiency ( K S ) and –Ψtlp was weak. Plant trait effects on v H were dominated by variation in K S, while effects of environment were dominated by variation in temperature. This research unifies hydraulics, photosynthesis and the leaf economics spectrum in a common theoretical framework, and suggests a route towards the integration of photosynthesis and hydraulics in land‐surface models.